A Review of the Optical Tomography System - Juliza Jamaludin; Rahim R.A.; Rahim H.A.; Fadzil N.S.M.; Rahiman M.H.F.; Jumaah M.F.; Muji S.Z.M.; Yunus M.A.M. (Penerbit UTM Press, 2024)
Non-Indexed Publication